Evolutionary Divergence of Platelet-Derived Growth Factor Alpha Receptor Signaling Mechanisms - Hamilton, T. Guy (American Society for Microbiology, 2003)
Receptor tyrosine kinases (RTKs) direct diverse cellular and developmental responses by stimulating a relatively small number of overlapping signaling pathways. Specificity may be determined by RTK expression patterns or by differential activation of individual signaling pathways. To address this issue we generated knock-in mice in which the extracellular domain of the mouse platelet-derived growth factor alpha receptor (PDGFαR) is fused to the cytosolic domain of Drosophila Torso (α(Tor)) or the mouse fibroblast growth factor receptor 1 (α(FR)). α(Tor) homozygous embryos exhibit significant rescue of neural crest and angiogenesis defects normally found in PDGFαR-null embryos yet fail to rescue skeletal or extraembryonic defects. This phenotype was associated with the ability of α(Tor) to stimulate the mitogen-activated protein (MAP) kinase pathway to near wild-type levels but failure to completely activate other pathways, such as phosphatidylinositol (PI) 3-kinase. The α(FR) chimeric receptor fails to rescue any aspect of the PDGFαR-null phenotype. Instead, α(FR) expression leads to a gain-of-function phenotype highlighted by ectopic bone development. The α(FR) phenotype was associated with a failure to limit MAP kinase signaling and to engage significant PI3-kinase response. These results suggest that precise regulation of divergent downstream signaling pathways is critical for specification of RTK function.